ARTIFICIAL INTELLIGENCE (AI) AND INTERNET OF THINGS (IOT): THREATS OR FUTURE FOR THE POLICE? - Reza, Alfin (Jurnal Ilmu Kepolisian, 2023)
This study examined the impact of Artificial Intelligence (AI) and Internet of Things (IoT) technologies in policing from the perspective of challenges, threats, and readiness. This study adapted a systematic literature review with data obtained from journals and previous research articles in 2020 â€“ 2023. Previous studies concluded that crime is the shadow of civilization; therefore, the police must be able to keep up with the times. The development of an increasingly modern civilization causes more complex crime, AI and IoT will cause unimaginable crime potential. Countries all over the world have invested in the development of AI and IoT technologies for crime prevention and detection. The idea behind this investment is to make the crime predictable and detectable, allowing the police to enforce the law exactly and properly. Â AI systems are expected to overcome several human deficiencies, such as consistency in analyzing situations from multiple data sources, especially millions of data points from IoT devices.